A Randomized Controlled Trial Evaluating the Effectiveness of Face-to-Face and Digital Training in Improving Child Mental Health Literacy Rates in Frontline Pediatric Hospital Staff - O'Connell, Jennifer; Shafran, Roz; Pote, Helen (Frontiers in Psychiatry, 2021)
Background: Children with chronic physical health conditions are up to six times more likely to develop a mental health condition than their physically well peers. Frontline paediatric hospital staff are in a good position to identify mental health problems and facilitate appropriate support for patients. To date, no evaluation of mental health literacy training has taken place with this professional group to enable early identification of difficulties. It is also not known whether face-to-face or digital training is more effective or preferable in this setting. To improve the skills of frontline hospital staff, a face-to-face and digital mental health literacy training course was delivered using MindEd content and evaluated in a randomised controlled trial. Method: Two-hundred and three frontline staff across different professions from a tertiary paediatric hospital were randomised to a face-to-face (n=64), digital (n=71), or waitlist control group (n=68). Face-to-face training was two and a half hours and digital training took approximately one hour. The effects of training were evaluated pre- and post-training and at two-week follow-up. Questionnaires assessed mental health knowledge, stigma, confidence in recognising concerns and knowing what to do, actual helping behaviour, as well as training delivery preference, completion rate and satisfaction. Results: Both face-to-face and digital training increased mental health knowledge, confidence in recognising mental health problems and knowing what to do compared to waitlist controls. Digital training increased actual help-seeking behaviour relative to the waitlist controls and stigma decreased across all groups. Staff were satisfied with both delivery methods but preferred face-to-face training. Conclusions: The results provide promising findings that digital content is an effective way of improving mental health literacy in frontline paediatric hospital staff. Providing digital training could be a time-efficient way of upskilling non-mental health professionals to identify mental health needs in a paediatric population and facilitate access to appropriate care.